Mrs. Everything : [large type] a novel - Weiner, Jennifer (Center Point Large Print, 2019)
"A smart, thoughtful, and timely exploration of two sisters' lives from the 1950s to the present as they struggle to find their places--and be true to themselves--in a rapidly evolving world"--